PENERAPAN PANCASILA PERSPEKTIF ISLAM - Khotimah, Husnul (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2020)
Regarding Pancasila Values ​​in the Islamic View, the first and second precepts constitute the Metaphysical Fundation, the third and fourth precepts constitute the Instrumental Fundation, and the fifth precepts constitute justice. Therefore we must do: mahasabah (evaluation), murakabah (guarding / supervising), and muhawalah (getting around) Islam as a religion that upholds egalitarianism, which is an open concept of solidarity and social dependence (ta`awun). Islam recognizes the right of all humans to live properly in terms of health, clothing, food, housing and social efforts that are needed regardless of differences in background. Islam also emphasizes the right of everyone to social security at the time of unemployment, illness, disability, widow / widower, elderly or disadvantaged. This standard of living is only possible in a healthy social order, where individuals with individuals, individuals with groups, and groups with groups maintain strong social relations. This has become the spirit of Islam in being responsible and sacrificing one another in order to create a community that shares, helps and helps each other. The piety of the faithful as slaves to Allah (‘abd Allah) boils down to a direct impact on piety in social-horizontal relations. These two aspects characterize the balance of Islamic teachings. Therefore, what should be our thoughts together is that the values ​​of Pancasila are substantially not in conflict with or even in accordance with Islam.